A constituição docente em matemática à distância: Entre saberes,experiências e narrativas - Diva Souza Silva (2010)
This doctorate thesis presents research finds of an investigation that sought comprehending the Teaching Constitution in Mathematics through a distance learning undergraduate course, when student-teacher' s practice knowledge meets student-teacher's higher education knowledge. This study was oriented to meet the following objectives: (i) identify, describe and analyze the trajectory of an entry group of student-teachers in an undergraduate Mathematics course, in a public university, in the state of Minas Gerais, in the Open University of Brazil (UAB) System; (ii) seek and narrate the process of teacher training and the process of professional activity knowledge acquisition before students-teachers entered the before mentioned mathematics undergraduate course; (iii) narrate and analyze, initially, the student-teacher's experience of living professional training development, via Distance Learning Education, when already is (in practice) a professional in service; next, the relation established between the privileged knowledge in scholar environment and the knowledge produced and mobilized by their professional practices. Anchored in the contributions of historical-cultural approaches, this doctorate thesis establishes a dialogue with theorists that discuss knowledge and teacher education in the field of Education and Mathematics' Education. The investigative path was guided by a qualitative approach and, inspired by Clandinin and Connelly (2000) and Bolivar (2002), a research methodology denominated Narrative Inquire. The empirical data were obtained through questionnaires, interviews, annotated memoirs of students education processes, observations and the records on the researcher field notes. Analysis and interpretation of this material was developed around three elements: (i) perception and motivations: the relationship with mathematics in their lives and (ii) perception of being a teacher: between knowledges and their encounter, (iii) perception of mathematics education in the distance learning education mode: a quest for presence in the absence. Results showed that speaking of Teaching Constitution in Mathematics through distance learning, between knowledges of practice and of academy, indicate proximities and distances. Proximities between being and doing manifested by the pursuit of theoretical framework and the articulation of different knowledge that amalgamate the teaching relation; distances for not understanding or not seeking to establish the relation between theory and practice, considered unnecessary for everyday practice that , in its turn, surrenders sometimes to the pragmatism. It is concluded that the experience of Teaching Constitution occurs throughout their lives from the very different student experiences and, for the subjects of this research, the teaching relation established even before entering higher education in the area. Finally, it was observed that students tried to make up for the absence by constituting study groups and ways of interaction among themselves. Distance Education was seen as a possible mode of learning to become a Mathematics teacher when articulating different types of knowledge and living practices. Knowledges encounters were an outcome of the search theory/empiricism in their own practice's ongoing reflection.